2012
DOI: 10.1371/journal.pone.0041838
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to BmNPV via Overexpression of an Exogenous Gene Controlled by an Inducible Promoter and Enhancer in Transgenic Silkworm, Bombyx mori

Abstract: The hycu-ep32 gene of Hyphantria cunea NPV can inhibit Bombyx mori nucleopolyhedrovirus (BmNPV) multiplication in co-infected cells, but it is not known whether the overexpression of the hycu-ep32 gene has an antiviral effect in the silkworm, Bombyx mori. Thus, we constructed four transgenic vectors, which were under the control of the 39 K promoter of BmNPV (39 KP), Bombyx mori A4 promoter (A4P), hr3 enhancer of BmNPV combined with 39 KP, and hr3 combined with A4P. Transgenic lines were created via embryo mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…The 39K promoter within this region had been previously used to express recombinant protein in baculovirus-insect expression system, and was capable of augmenting the level of foreign gene expression (Lin and Jarvis, 2013;Toth et al, 2014). However, this region of 39K was missing when the promoter was used for pathogen induction (Jiang et al, 2012a;Zhang et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 39K promoter within this region had been previously used to express recombinant protein in baculovirus-insect expression system, and was capable of augmenting the level of foreign gene expression (Lin and Jarvis, 2013;Toth et al, 2014). However, this region of 39K was missing when the promoter was used for pathogen induction (Jiang et al, 2012a;Zhang et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, controlled by p39K (p-151) promoter, the RNAi expression system was activated by BmNPV infection, which in turn blocked virus proliferation. Recently, studies on BmNPV resistance in silkworm demonstrated that expression of an anti-pathogen factor controlled by hr3-39k can be activated upon infection (Jiang et al, 2012a;Zhang et al, 2014b), while the hr3-39k promoter shows weaker activity that causes lower expression level of foreign genes following infection in transgenic pears. In this study, the RNAi system was regulated by an efficient BmNPV-inducible HP39K promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used actin-1 (A1) (Li et al 2014), actin-3 (A3) (Gao et al 2014b;Wang et al 2014Wang et al , 2015Kolliopoulou et al 2015), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (Bao et al 2009), translation initiation factor 3 (TIF-3) (Zhou et al 2013), TIF-4A (also known as sw22934) (Jiang et al 2012a(Jiang et al , b, 2013b, and 18S rRNA (Xue et al 2012) as housekeeping genes in silkworms. Importantly, because use of unsuitable RGs may lead to incorrect interpretation of gene expression patterns and functions (Velada et al 2014), the correct selection of RGs is required.…”
Section: Introductionmentioning
confidence: 99%
“…BmNPV is a serious viral pathogen in sericulture industry, and no effective drug or specific prevention is available to date. Researchers gave major attention to inhibition of the virus replication by over-expression of antiviral exogenous gene [2] or RNA interference [3,4]. However, mechanisms of BmNPV BV entry into the host cell have not been addressed.…”
Section: Introductionmentioning
confidence: 99%